2013
DOI: 10.1155/2013/497585
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Functional Gastrointestinal Disorders in the Chinese Air Force Population

Abstract: Background. Functional gastrointestinal disorders (FGIDs) are common in the general population worldwide. However, there is paucity of large sale surveys for prevalence of FGID in the military personnel. Methods. It is a cross-sectional study, using Rome III criteria for the diagnosis of FGID among the Chinese Air Force (CAF) workers. Results. Of 4633 registered male subjects, there were 818 (16.4%) air crew and 4170 (83.6%) ground personnel. FGIDs were identified in 1088 (23.48%) of cases. It was more prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 25 publications
5
16
3
Order By: Relevance
“…Other population-based studies have reported a lower incidence of FGID (26.2 %) than this [8] suggesting a wide variation of FGID among deferent populations. Still fewer studies have been conducted in a tertiary care setting.…”
Section: Demographycontrasting
confidence: 50%
“…Other population-based studies have reported a lower incidence of FGID (26.2 %) than this [8] suggesting a wide variation of FGID among deferent populations. Still fewer studies have been conducted in a tertiary care setting.…”
Section: Demographycontrasting
confidence: 50%
“…Moreover, about 37% of soldiers were aged over 25 (13.1% were in age >35). 20 According to the another study of Chinese college and university students of the young age group, the prevalence of total FGIDs was 23%. 10 However, considering the fact that FGIDs are more prevalent in females, the results of our study may agree with those of the Chinese study.…”
Section: Discussionmentioning
confidence: 99%
“…This result is lower than that from a study of Chinese air force population (23.5%). 20 However, among the 4,170 soldiers, 1,070 officers with higher education and longer years of service were included in that study. Moreover, about 37% of soldiers were aged over 25 (13.1% were in age >35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It would be interesting to know whether FGIDs are also prevalent among military personnel and what type of FGID is predominant in the armed forces. A population-based survey of the Chinese air force [ 28 ] revealed that more than 23 % of air crew and ground personnel reported gastrointestinal symptoms that fulfilled the Rome III criteria for FGIDs. Additionally, a German study reported that approximately 50 % soldiers who sought health care for gastrointestinal problems [ 29 ] were diagnosed with FGIDs.…”
Section: Reviewmentioning
confidence: 99%